A varactor-based 1024-element RIS design for mm-waves - da Silva, Luis G.; Chu, Z.; Xiao, Pei; Cerqueira S, Arismar (Frontiers in Communications and Networks, 2023)
This paper reports a reconfigurable intelligent surface (RIS) for beamforming and beam steering applications operating in the millimeter wave (mm-waves) frequency band. The proposed 2-bit RIS design is implemented using a radar cross-section (RCS) approach in ANSYS HFSS for performance evaluation and system-level analysis. It is based on split-ring resonator (SRR) unit cells, tuned by varactor diodes, comprising 1,024 elements arranged in a 32 × 32 matrix with linear gradient phase configuration operating at 24.5 GHz over the fifth generation of mobile communications New Radio (5G NR) frequency range 2 (FR2). A beam steering from −60° to 60° in the azimuth plane is demonstrated for mm-waves coverage extension. Numerical simulations of RCS patterns from −10° to −60° and from 10° to 60° with approximately 3 dB scan loss manifest the applicability of the proposed RIS towards the sixth generation of mobile communications (6G). Furthermore, simulated results of angular reciprocity prove the RIS response up to 110° under an oblique incident wave at 60°. To the best of our knowledge, this is the highest RIS angular reciprocity reported in the literature, validating its application to coverage extension from −60° to 60°. In addition, the RCS level and reflected angle relationship are modeled for system-level analysis purposes.